Estafilococos em hambúrguer artesanal - Costa, Antonio Cleyton Arruda de Azevedo (2018)
The processing of meat products in the industry aims to increase the useful life of the product, as well as the full use of the parts of the animals and among these meat products, the hamburger stops being a coadjuvant and become a main food due to its practicality and nutritional characteristics, due to the high manipulation of the food, it is subject to microbiological contamination by deteriorating and pathogenic agents, which may lead to food-borne diseases, such as staphylococcal intoxications. In addition, some pathogenic microorganisms present antimicrobial resistance genes which generate a public health related to the antibiotic therapy of patients affected by food-borne diseases. In view of this problem, the present work aimed to evaluate the microbiological quality of the handcraft hamburgers commercialized in Mossoró, RN and to verify the molecular profile of toxin production and staphylococcal antimicrobial resistance of nine establishments specializing in handcraft hamburger. To achieve the objectives, the counts of mesophilic microorganisms and staph was successfully carried out in Mossoró, RN, as well as the search for enterotoxin production genes and the antimicrobial resistance profile of Staphylococcus aureus isolated from hamburgers. After the analysis, all samples showed high contamination of mesophilic microorganisms (5.2 to 6.7 log CFU / g). Staphylococcal counts showed that three establishments were outside the standard (3.7, 5.4, 4.3 log CFU / g), but there was growth of coagulase positive staphylococci in samples from four establishments (1, 4, 5 and 7) from the four, three, four, five, seven, seven, five, seven, seven, five, seven, seven, seven, of antimicrobial resistance, and the antibiogram revealed that of the nine antibiotics tested, five no longer had any action against the Staphylococcus aureus isolated the four establishments. With this, it can be inferred that, although the legislation allows a maximum number of microorganisms in the food, they can produce toxins and resist the various antibiotics of clinical use, making it difficult for the patient to be treated, as well as the manipulation and / or storage of the food is being carried out in an inadequate manner, requiring greater rigidity in good handling practices, as well as in legislation